A company profile and a franchising brochure for mister donut - Enriquez, Phoebe Marie J. (Animo Repository, 1997)
The thesis project is a print production package entitled A Company Profile and a Franchising Brochure for Mister Donut. Mister Donut under new management - now a division of Food Fest Incorporation, did not have any formal company profile. This communication tool is needed to serve as a source of information for new and old employees, current franchise owners, and potential investors. The company profile that the proponents produced is the first formal literature of the company. It serves as a source of information about the company's organizational structure, the new management's mission vision, philosophy, objectives, and goals. It also contains the history of Mister Donut and how it came about in the Philippines. The second project the proponents produced is a three fold franchising brochure that serves as a marketing campaign tool for the company. It integrated information about Mister Donut and an application form for franchising the Mister Donut trademark.